The anticoagulation length of therapy and risk of new adverse events in venous thromboembolism (ALTERNATIVE) study: Design and survey results - Portugal, Cecilia; Fang, Margaret C.; Go, Alan S.; Zhou, Hui; Chang, John; Prasad, Priya; Fan, Dongjie; Garcia, Elisha A.; Sung, Sue Hee; Reynolds, Kristi (PloS one, 2022)
The Anticoagulation Length of Therapy and Risk of New Adverse Events In Venous Thromboembolism (ALTERNATIVE) study was designed to compare the benefits and harms of different treatment options for extended treatment of venous thromboembolism (VTE). In this paper, we describe the study cohort, survey data collection, and preliminary results. We identified 39,605 adult patients (age ≥ 18 years) from two large integrated health care delivery systems who were diagnosed with incident VTE and received initial anticoagulation therapy of 3 months or longer. A subset of the cohort (12,737) was invited to participate in a survey. Surveys were completed in English, Spanish or Mandarin via a mailed questionnaire, an online secure web link, or telephone. The survey domains included demographics, personal medical history, anticoagulant treatment history, anticoagulant treatment satisfaction, health-related quality of life and health literacy. A total of 5,017 patients participated in the survey for an overall response rate of 39.4%. The mean (SD) age of the survey respondents was 63.0 (14.5) years and self-reported race was 76.0% White/European, 11.1% Black/African American, and 3.8% Asian/Pacific Islander and 14.0% reported Hispanic ethnicity. Sixty percent of respondents completed the web survey, while 29.0% completed the mail-in paper survey, and 11.0% completed the survey via telephone. The ALTERNATIVE Study will address knowledge gaps by comparing several treatment alternatives for the extended management of VTE so that this information could be used by patients and clinicians to make more informed, patient-centered treatment choices.